Biomes as evolutionary arenas: Convergence and conservatism in the trans‐continental succulent biome. Issue 7 (10th March 2020) - Ringelberg, Jens J.; Zimmermann, Niklaus E.; Weeks, Andrea; Lavin, Matt; Hughes, Colin E.
Abstract: Aim: Historically, biomes have been defined based on their structurally and functionally similar vegetation, but there is debate about whether these similarities are superficial, and about how biomes are defined and mapped. We propose that combined assessment of evolutionary convergence of plant functional traits and phylogenetic biome conservatism provides a useful approach for characterizing biomes. We focus on the little‐known succulent biome, a trans‐continentally distributed assemblage of succulent‐rich, drought‐deciduous, fire‐free forest, thicket and scrub vegetation as a useful exemplar biome to gain insights into these questions. Location: Global lowland (sub)tropics. Time period: Present. Major taxa studied: Angiosperms. Methods: We use a model ensemble approach to model the distribution of 884 species of stem succulents, a plant functional group representing a striking example of evolutionary convergence. Using this model, phylogenies, and species occurrence data, we quantify phylogenetic succulent biome conservatism for 10 non‐succulent trans‐continental plant clades including prominent elements of the succulent biome, representing over 800 species. Results: The geographical and climatic distributions of stem succulents provide an objective and quantitative proxy for mapping the distribution of the succulent biome. High fractions of succulent biome occupancy across continents suggest all 10 non‐succulent study clades are phylogenetically conserved within the succulent biome. Main conclusions: The trans‐continental succulent and savanna biomes both show evolutionary convergence in key biome‐related plant functional traits. However, in contrast to the savanna biome, which was apparently assembled via repeated local recruitment of lineages via biome shifts from adjacent biomes within continents, the succulent biome forms a coherent trans‐continental evolutionary arena for drought‐adapted tropical biome conserved lineages. Recognizing the important functional differences between the succulent‐rich, grass‐poor, fire‐free succulent biome and the grass‐dominated, succulent‐poor, fire‐prone savanna biome, and defining them as distinct seasonally dry tropical biomes, occupying essentially non‐overlapping distributions, provides critical insights into tropical biodiversity and the extent of biome stasis versus biome shifting.